2020
DOI: 10.4314/ejhs.v30i4.9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Capital and Self-Efficacy in Women with Gestational Diabetes Mellitus: A Cross Sectional Study

Abstract: BACKGROUND: Self-efficacy is one of the most likely determinants of glucose self-management and self-monitoring by diabetic patients. Also, social capital is one of the effective social factors that may affect health behaviors. The aim of this study was to evaluate the relationship between social capital and selfefficacy in women with gestational diabetes mellitus (GDM).METHODS: This descriptive- analytical cross-sectional study was conducted on 212 women with GDM in two diabetes center in Mazandaran, north of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…HL had a weaker effect on self-efficacy and acted as a partial mediator in the process of social support influencing self-efficacy. Moghadam et al (57) found that the dimensions of social capital such as community involvement, neighborhood, family and friends, tolerance of diversity, and work relationships were influential factors in the self-efficacy of women with GDM, the enhancement of women's social capital may increase their self-efficacy in controlling GDM. Self-efficacy represents the confidence and ability of pregnant women with GDM to engage in self-management in some extent, which can alleviate the stress level, improve the quality of life of women with GDM (46), and motivate them to adopt a healthy lifestyle after diagnosis (58).…”
Section: Discussionmentioning
confidence: 99%
“…HL had a weaker effect on self-efficacy and acted as a partial mediator in the process of social support influencing self-efficacy. Moghadam et al (57) found that the dimensions of social capital such as community involvement, neighborhood, family and friends, tolerance of diversity, and work relationships were influential factors in the self-efficacy of women with GDM, the enhancement of women's social capital may increase their self-efficacy in controlling GDM. Self-efficacy represents the confidence and ability of pregnant women with GDM to engage in self-management in some extent, which can alleviate the stress level, improve the quality of life of women with GDM (46), and motivate them to adopt a healthy lifestyle after diagnosis (58).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning GDM, it was found among other studies worldwide a strong positive relationship between self-efficacy and GDM self-control [50][51][52][53][54]. Self-efficacy was also highly correlated with improving self-management among individuals with DM in several studies [55][56][57][58][59][60].…”
Section: Plos Onementioning
confidence: 99%
“…In order to improve self-efficacy, some researchers have employed the individual social capital as a predictor. According to Hasani Moghdam and some other colleagues, there has been a positive impact of individual social capital on self-efficacy among women in Iran (Hasani Moghadam et al, 2020). And the other scholars have investigated the facilitating function of individual social capital on self-efficacy for high school students in China (Liu & Ngai, 2020); among the young with job in Swede (Andersson, 2021).…”
Section: Social Capital Self-efficacy and Life Satisfactionmentioning
confidence: 99%
“…In addition, there also have been researchers conducting studies, demonstrating the positive association of individual social capital with self-efficacy (Andersson, 2021;Hasani Moghadam, Yousefi Abdolmaleki, Alijani, Bagherian Afrakoti, & Ganji, 2020;Hudson, Hagedoorn, & Bubeck, 2020;Liu & Ngai, 2020). Nevertheless, the relationship among the three above constructs remains unclear, and the aim of this study tries to bridge the gap by jointing them collaboratively.…”
Section: Introductionmentioning
confidence: 99%